Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.apmr.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Member Factors Influencing Outcomes of Poststroke Inpatient Rehabilitation

Abstract: Patients' intention of independence positively affected motor recovery, while family members' positive attitudes promoted cognitive regain. The findings suggested plausible age-related differences in how patients' intentions affect emotion versus self-care independence outcomes. Future studies should explore strategies for promoting positive attitudes toward independence among patients and family members during poststroke rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…Global cognitive ability and memory were evaluated by using the Fuzhou version of the MoCA (Fang et al, 2017) and Wechsler's Memory Scale (Elwood, 1991). Global cognitive function was measured using the Fuzhou version of the MoCA scale, which is a brief test that evaluates visuospatial/executive functions, naming, verbal memory registration and learning, attention, abstraction, delayed verbal memory and orientation.…”
Section: Cognitive and Physical Frailty Assessmentmentioning
confidence: 99%
“…Global cognitive ability and memory were evaluated by using the Fuzhou version of the MoCA (Fang et al, 2017) and Wechsler's Memory Scale (Elwood, 1991). Global cognitive function was measured using the Fuzhou version of the MoCA scale, which is a brief test that evaluates visuospatial/executive functions, naming, verbal memory registration and learning, attention, abstraction, delayed verbal memory and orientation.…”
Section: Cognitive and Physical Frailty Assessmentmentioning
confidence: 99%
“…Stroke family caregivers have widely reported physical symptoms and psychological distress (Cameron, Stewart, Streiner, Coyte, & Cheung, 2014;Kamel et al, 2009). Along with the decline of caregivers' physical and psychological well-being, their ability and willingness to provide care to the stroke survivors are weakened, resulting in a reduced quality of care which directly or indirectly affects the recovery and well-being of the stroke survivors (Fang et al, 2017).…”
mentioning
confidence: 99%
“…The MoCA-BJ 30 was created when the Montreal Cognitive Assessment was first adapted for use in China. Due to the large land area of China and the imbalance of medical and cultural development among its various regions, Fang et al 31 also found deficiencies in the clinical application of Montreal Cognitive Assessment and developed the MoCA-ChiFZ.…”
Section: Resultsmentioning
confidence: 99%